Environmental effect of conventional and gm crops of cotton (gossypium hirsutum l.) and corn (zea mays l.) (2011)
In the corn belt of Valle de San Juan and in the cotton zone of El Espinal, municipalities in the department of Tolima (Colombia), 10 conventional corn producers, 10 producers of genetically modified corn, five producers of conventional cotton and 15 producers of transgenic cotton were surveyed in the first half of 2009 to contrast the differences in the environmental impact associated with use of insecticides and herbicides, which were evaluated by estimating the environmental index quotient-EIQ. In the case of maize, an EIQ of 42 was found in the conventional type, while transgenic technology had an EIQ of 3.03. In the cultivation of cotton, an EIQ of 263.59 was found for the conventional type while for transgenic technology this value varied between 335.75 (Nuopal BG/RR) and 324.79 (DP 455 BG/RR). These data showed a lower environmental impact using GM technology in the cultivation of maize when compared to the conventional counterpart, in connection with the use of insecticides and herbicides, in the context of time, space and genotypic analysis. This effect was not observed in the case of cotton, where environmental impacts were similar.